Nigritella nigra Rchb. ... - Jarvis, Charlie (Linnaean Society of London in association with the Natural History Museum, 2007)
Satyrium nigrum Linnaeus, Species Plantarum 2: 944. 1753. "Habitat in Alpibus Helveticis, Lapponicis." RCN: 6835. Lectotype (Baumann & al. in Mitteilungsbl. Arbeitskr. Heim. Orchid. Baden-Württemberg 21: 507, Abb. 30. 1989): Sweden. Jämtland, Hagström, Herb. Linn. No. 1055.4, "planta dextra" (LINN). Current name: Nigritella nigra (L.) Rchb. (Orchidaceae). ... : Published as part of Jarvis, Charlie, 2007, Chapter 7: Linnaean Plant Names and their Types (part S), pp. 806-877 in Order out of Chaos. Linnaean Plant Types and their Types, London :Linnaean Society of London in association with the Natural History Museum on page 819, DOI: 10.5281/zenodo.291971 ...